ISO 9001 QMS - Impact on the Organizational Performance of Suppliers and Vendors: Case Study of Modenas - Mohd Akhir, Ahmad (2010)
This study has identified to what extent the impact of organizational performance of suppliers and vendors by absorbing quality management system IS0 9001. Moreover, this study also determines the organizational performance of suppliers and vendors before and after adopting the IS0 9001 quality management system(QMS). Especially the research framework was developed from a case study conducted at Motorcycle and Engine Nasional Sendirian Berhad (MODENAS)as the supplier for a total of 97 companies working as vendors for MODENAS. The data was collected from several sources, including primary and secondary data, which included monitoring vendors' performance. The results have indicated that significant improvements of supplier organization performance such as productivity results had increased to 80 percent: Straight Pass had increased to 87 percent: Warranty claims had fallen to 0.12 percent. In conclusion, this study provided insight and further understanding on how other sector could adopt IS0 9001 quality management system into their vendors that would provide better organizational performance.